The Effect of Chemical and Bio-fertilizer Source of Nitrogen on Qualitative and Quantitative Yield of Saffron (Crocus sativus L.) - H Omidi; H Naghdi Badi; A Golzad; H Torabi; MH Footoukian (Institue of Medicinal Plants, ACECR, 2009)
Background: Biofertilizers are an alternative to mineral fertilizers for increasing soil productivity and plant growth in sustainable agriculture. Therefore, it is necessary to determine the effects of biofertilizers on valuable medicinal plants such as saffron. Objective: To determine the effects of chemical and bio-fertilizer nitrogen on quantitative yield and some quality components of saffron (Crocus sativus L.). Methods: This study has been conducted in Absard region, north of Tehran, Iran along 2006-2008 in a randomized complete block design with three replications and four fertilizer treatments. The treatments were n1 (Control or no applying nitrogen fertilizer), n2 (150 kg/ha nitrogen as urea), n3 (5 kg/ha bio-fertilizer as Nitroxine) and n4 (a mixture of 2.5 kg/ha bio-fertilizer as Nitroxine + 75 kg/ha nitrogen as urea). Results: The results showed that fertilizer treatments had significant effects (p<0.01) on fresh stigma and style length, leaf length, leaf number, saffron yield (dry weight of stigma and style), and content of Safranal, Crocine and Picrocrocine. Although the maximum yield of stigma and style were obtained in n2 treatment (150 kg/ha nitrogen) and n4 (a mixture of 2.5 kg/ha bio-fertilizer as Nitroxine + 75 kg/ha nitrogen as urea), the application of bio-fertilizer (n3) increased the saffron yield about 0.83% more than control treatment. However, n3 (5 kg/ha bio-fertilizer as Nitroxine) was the best treatment in respect of safranal and picrocrocine content. Also, the maximum content of crocine was obtained in n4 (a mixture of 2.5 kg/ha bio-fertilizer as Nitroxine + 75 kg/ha nitrogen as urea). Conclusion: Application of the chemical/bio- fertilizer increased qualitative and quantitative Yield yield of saffron. Also, the application of nitroxine can be in order to reduction in application of nitrogen fertilizer in agro-ecosystem which is attitude toward the minimize of environmental pollution and sustainable agriculture.